Are foreign multinationals more efficient? A stochastic production frontier analysis of Malaysia's automobile industry - Khalifah, Noor Aini; Abdul Talib, Basri (Universiti Utara Malaysia, 2008)
This paper compares the sources of total factor productivity (TFP) growth of foreign (establishments with 51% and above foreign equity ownership) and local establishments in Malaysia’s automotive sector by applying a stochastic production frontier to a panel of 510 plants for the period 2000-2004. The results showed that TFP growth for local automobile plants was minimal at 0.63% and minimally negative at -0.27% for foreign plants. On average,over the study period, technical efficiency changes contributed positively toward TFP growth but scale efficiency changes were negative for both local and foreign establishments. Technical progress was minimally positive for local establishments and minimally negative for foreign establishments.The small size of plants and the lower share of white-collar workers were significant in explaining plant inefficiency in Malaysia’s automobile sector. A higher capital-labour ratio was positively related to plant inefficiency and this may be due to excess capacity in the automobile sector as a result of a small domestic market. Finally, foreign multinationals are significantly more efficient than locally owned plants.